Managing the online learning revolution in an MBA course:quality assurance through strategic development - Ladyshewsky, Richard; Soontiens, Werner (Maastricht School of Management, 2013)
As online education becomes more commonplace so does the competition for students and the concomitant need to keep up with technology and best practice. In an environment where massive open online courses (MOOCs) are proving to be a disruptive innovation to university education the impact is shifting the boundaries of online delivery and revolutionising online learning. Despite its rapid rise and relative populist approach there remain uncertainties around notions of student performance, the student experience and overall aspects of academic quality assurance of MOOCs. This is particularly important in a higher education environment characterised by regulatory requirements and driven by international accreditation, both of which tend to apply an increased scrutiny on the delivery of online education. In the business education sphere this appears to culminate in the global MBA market that may soon see direct competition from MOOC providers.This paper considers an approach taken to manage academic quality assurance and delivery of an online MBA course, mostly delivered in an asynchronous environment. It discusses the strategic intent and subsequent steps taken to operationalize its various components. Key elements of the plan include the allocation of staff resources including the appointment of an academic online MBA program leader and a dedicated instructional design team. In addition, a range of support mechanisms and instruments were developed and made available to online instructors to facilitate both the development of the required skillset and continuous improvements.The strategic approach pivots around the development and implementation of quality assurance (QA) mechanisms and audits, over and above the existing QA measures used for face to face delivery such as course reviews and an extensive student feedback mechanism. The additional audits on 'course delivery against strategic plan' and 'instructor engagement' ensure the implementation of a threshold for online course delivery facilitates the roll-out of good practice across the program and allows for remedial actions when required. In addition, the online delivery is supported by an electronic lounge in an effort to establish an MBA wide community. It appears that a strategic approach to the delivery of online university education, particularly with an embedded focus on academic quality assurance has not only contributed to the development of a structured and systematic approach and skillset for online instructors but likewise delivered desired outcomes. Ultimately, the education revolution seems to have taken another quantum leap forward, and a focus on quality assurance can only bode well for any provider, particularly when product differentiation becomes crucial.